2023
DOI: 10.1155/2023/2587551
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Carbon Nanofiber-Modified Concrete in Industrial Building Design

Abstract: In order to explore the influence law and action mechanism of carbon nanofibers on the basic mechanical properties of concrete, the author proposes the mechanical properties and microscopic mechanism of carbon nanofiber-modified concrete. Concrete was prepared with different dosages of carbon nanofibers, and the compressive strength, flexural strength, and splitting strength of carbon nanofiber-modified concrete were tested, and the modification mechanism was explored. Experimental results show that an appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Due to the previous advantages, nanofibers have many applications such as drug delivery systems [30], industrial building design [31], biomedicine [32,33], 4D printing industry [34], textile industry [35,36], and wastewater remediation [37]. Nanofibers could be produced by electrospinning and non-electrospinning techniques (Figure 2).…”
Section: Nanofibers In Water Energy and Foodmentioning
confidence: 99%
“…Due to the previous advantages, nanofibers have many applications such as drug delivery systems [30], industrial building design [31], biomedicine [32,33], 4D printing industry [34], textile industry [35,36], and wastewater remediation [37]. Nanofibers could be produced by electrospinning and non-electrospinning techniques (Figure 2).…”
Section: Nanofibers In Water Energy and Foodmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%